Firm Mortality and Natal Financial Care - Bhattacharya, Utpal; Borisov, Alexander; Yu, Xiaoyun (Journal of Financial and Quantitative Analysis, 2015)
Abstract We construct a mortality table for U.S. public companies during 1985–2006. We find that the age-specific mortality rates of firms initially increase, peaking at age three, and then decrease with age, implying that the first 3 years of public life are critical. Financial intermediaries involved around the “public birth” of a firm (e.g., venture capitalists (VCs) and high-quality underwriters) are associated with lower firm mortality rates, sometimes for up to 7 years after the initial public offering (IPO). VCs reduce mortality rates more through natal financial care than through selection, whereas high-quality underwriters affect firm mortality more through selection.